An Analysis of Academic Stress, Contributing Factors, and Coping Mechanisms Among Foreign Language Students in A Private University In Makassar - Ainun Fauziah Fadly; Muhammad Tahir; Muhammad Arham (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
This study investigates academic stress among students of the English Literature Study Program at Universitas Muslim Indonesia (UMI), Makassar, South Sulawesi. The objectives were: (1) to identify the main sources of academic stress, (2) to analyze internal and external contributing factors, and (3) to examine coping mechanisms employed by students across different semesters. A qualitative case study approach was applied, using semi-structured interviews as the primary instrument, followed by thematic analysis of responses from first, third, and seventh semester students. Findings revealed that stress evolves with academic progression: first-semester students experienced adjustment-related stress, third-semester students reported performance pressure and fear of failure, and seventh semester students faced graduation-related stress. Contributing factors included self-expectation, low self-efficacy, poor time management, family expectations, peer competition, and language challenges, while institutional factors were less significant. Coping mechanisms varied across semesters, ranging from personal relaxation, hobbies, and prayer to peer collaboration and institutional support, with clear gender differences in coping preferences. The study concludes that academic stress at Universitas Muslim Indonesia is dynamic and culturally embedded. It recommends semester-specific and gender-sensitive interventions, including strengthening self-efficacy, promoting adaptive coping strategies, enhancing family engagement, and providing institutional support to foster resilience and student well-being.